Animal/human: proximities and borders in Mundo Animal and other texts by Antonio Di Benedetto (Anclajes, 2018)
Antonio Di Benedetto (1922-1986), one of the most important Argentinean writers of the twentieth century, published in 1953 Mundo Animal, a volume of short stories in which the animal figure becomes fundamental, as its title makes explicit. Within the fictional universe of the work, this figure is incarnated in the human and vice versa, suggesting that humanity, beyond its exclusive attributes ―reason and language―, shares a broad common substratum with other living beings. This existential configuration not only provokes hesitations in the reader, but has also ontological implications, that is, it leads to questioning about meaning schemes and the human condition in these fantastic-allegorical stories. The purpose of this paper is then to investigate and interpret Di Benedetto’s fictionalization of these encounters and borders between the animal and the human, analyzing different textual manifestations of this question: the quid pro quo procedure, the non-human narrators, the animality of children, the relationship with psychic pathologies, the ontological proximity between the two worlds, the metaphor of the mirror, and the corporality.
Keywords: Argentine literature; XXth Century; Antonio Di Benedetto; animality